Application of Maltodextrin as Chiral Selector in Capillary Electrophoresis for Quantification of Amlodipine Enantiomers in Commercial Tablets. Issue 8 (16th May 2014) - Nojavan, Saeed; Pourmoslemi, Shabnam; Behdad, Hamideh; Fakhari, Ali Reza; Mohammadi, Ali
ABSTRACT Maltodextrin was investigated as a chiral selector in capillary electrophoresis (CE) analysis of amlodipine (AM) enantiomers. For development of a stereoselective CE method, various effective parameters on the enantioseparation were optimized. The best results were achieved on an uncoated fused silica capillary at 20 °C using phosphate buffer (100 mM, pH 4) containing 10% w/v maltodextrin (dextrose equivalent value 4–7). The UV detector was set at 214 nm and a constant voltage of 20 kV was applied. The range of quantitation was 2.5–250 µg/mL (R2 > 0.999) for both enantiomers. Intra‐ (n = 5) and interday (n = 3) relative standard deviation (RSD) values were less than 7%. The limits of quantitation and detection were 1.7 µg/mL and 0.52 µg/mL, respectively. Recoveries of R(+) and S(−) enantiomers from tablet matrix were 97.2% and 97.8%, respectively. The method was applied for the quantification of AM enantiomers in commercial tablets. Also, the enantioseparation capability of heparin was evaluated and the results showed that heparin did not have any chiral selector activity in this study. Chirality 26:394–399, 2014. © 2014 Wiley Periodicals, Inc.